ألكلام عن البديع : تاريخه وأقسامه - Didin Faqihudin (Hunafa: Jurnal Studia Islamika, 2007)
This article  deals with one aspect of balaghah i.e. badi’. As we know badi’ is a science by which we know some beautiful features of sentences. But how  badi’ emerged in the history of Arabic culture? Who is responsible for the rising of  badi’? And how many parts  badi’ has? This article  tries to answer these questions. Kata Kunci : ‘ilm al-badi’,’ilm al-balagah, ‘ilm al-bayan,’ilm al- ma’ani